HYDROLOGICAL ENVIRONMENTAL IMPACTS CAUSED BY DEFORESTATION UNDERGROUND: PETROPOLIS, RJ - Tamara Magalhães da Silva; Thereza Cristina Ferreira Camello; Josimar Ribeiro de Almeida (Universidade do Estado do Rio de Janeiro, 2015)
<!-- p { margin-bottom: 0.25cm; direction: ltr; line-height: 120%; text-align: left; widows: 2; orphans: 2; }p.western { font-size: 11pt; }p.cjk { font-size: 11pt; }p.ctl { font-size: 11pt; }a:link { color: rgb(0, 0, 255); }a.western:link { }a.cjk:link { }a.ctl:link { font-family: "Times New Roman"; } --> Urban expansion in Petropolis region is due to massive deforestation for housing and other human activities. Deforestation is the main cause ecological imbalances, resulting in: flooding, decrease in porosity and desertification of soil. By AIA semi-qualitative technique analysis it studied possible losses and benefits of urban expansion in the locality, if changes were likely or not of occurrence and their level of impaction. It was observed that the probability of occurrence of damage was much higher than that of benefits. The result corroborates the literature, therefore, has been seen that vegetation plays an important role in water control of the town, and also in the physical and chemical soil. The probability of catastrophic consequences, due to deforestation, is extremely high, and even mid-sized consequences have capacity of environmental impacts that are likely to be irreversible. Deforestation intensifies the consequences of major frequent rainfall in the summer of the State of Rio de Janeiro, so the higher the deforestation, the greater the likelihood of recurrent and intense rainfall events resulting from large. Therefore, it is necessary to control urban sprawl in the region to reduce water environmental impact in the region.   DOI: http://dx.doi.org/10.12957/sustinere.2015.17327